Respostas

2013-07-30T16:01:41-03:00
F(x) = -3x + 3
a)                            b)                           c)                         d)
-3x + 3 = 11              -3x + 3 = 17           -3x + 3 = -34           -3x + 3 = -154
-3x = 11 - 3               -3x = 17 - 3            -3x = -34 - 3            -3x = -154 - 3
-3x = 8                      -3x = 14                -3x = -37                  -3x = -157
x = -8/3                      x = -14/3               x = -37/-3                 x = -157/-3
                                                             x = 37/3                   x = 157/3